Advocating for an Advanced Cardiac POCUS Curriculum Among Internal Medicine Residents - Oseiwe B. Eromosele; Alexandra Pipilas; Jason A. Sherer; Michael C. Schwartz (Journal of Medical Education and Curricular Development)
Advocating for integrating a cardiac point-of-care ultrasound (POCUS) curriculum into Internal Medicine residency, this letter emphasizes the unique advantages of cardiac POCUS, particularly its rapid utility and safety, while highlighting existing knowledge gaps among trainees. This perspective research letter underscores the need for a structured advanced cardiac POCUS elective to address the knowledge and skill gaps among internal medicine trainees who have taken the introductory POCUS elective, providing a career preparatory course for internal medicine residents interested in cardiology, critical care, hospital medicine, primary care, and rural medicine. The perspective research paper also underscores the feasibility and benefits of such training, ultimately supporting the implementation of an advanced cardiac POCUS elective in the United States Internal Medicine residency programs.